Word Formation Mastery in Efl Context : An Inquiry Into Derivational Processes in Student Writing - Agusti Rahayu; Siska Bochari; Sriati Usman; Hastini Hastini (Badan Penerbit STIEPARI Press, 2025)
This study analyzed the use of derivational suffixes that transform root nouns into adjectives in the writing of EFL students at Tadulako University. This study aims to identify the types of adjectival suffixes that are difficult to use and the common errors students make. Using quantitative descriptive method, data were collected from the students' writings and analyzed morphologically. The results show that suffixes such as -ful, -ous, -ly, -al, -ic, -able, -less, and -ive are frequently used. However, many errors were found, especially in choosing the wrong suffixes and in spelling. These findings highlight the need for more explicit instruction in morphological rules to help the students form words more accurately.